FAKTOR - FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN LQ-45 YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2014 - Eka Apriyani Setianingrum, 12.05.52.0132; Suwarti, Titiek (Students' Journal of Accounting and Banking, 2016)
This study aimed to analyze the factors affecting capital structure. Profitability measured by the capital structure, company size, liquidity, asset structure and growth of assets. The sample was LQ 45 listed company on the Stock Exchange in 2010-2014 by using purposive sampling method. Total sample was 85 companies that meet the criteria as a sample of this research. Methods of analysis of this study using multiple linear regression analysis. The results of this study indicate that profitability was  significant effect on the capital structure. Firm's size, liquidity, asset structure and growth in assets have a significant effect on the capital structure. Limitations of this study is to use the LQ 45 companies whose shares are listed on the Indonesia Stock Exchange (BEI) as the research object, so that research results can not be drawn the conclusion for each industry sector. Keywords: Capital Structure, Profitability, Company Size, Liquidity, Asset Structure, Growth Assets